(3JMOjGJ GdCef GdZPGFjs - (3GdUGOb YhV(B, (3HTjQs ((3HjQhJ(B:s (3GdOGQ GdYQHjI ddYdhe(B,s, 2009)
(3GdHYO GdOhdj h GdYQHj dCReI GdZPGA h JOGYjGJgG h eTcdI GdGef GdZPGFj GdYQHj h JMOjGJgG , JMdd h Jbhje GdeTcdI h GdYdGL GdebJQM dMd GdeTcdI h QFjI hGbYjI dTQGcI EfJGLjI Vef GSJQGJjLjI HQGLeGJjI dMd GdeTcdI eY hLhO GSJQGJjLjI GdJfejI GdRQGYjI GdYQHjI GdeSJOGeI ddYbOjf (B2005 2025s
Keywords: (3GdCef GdZPGFjs; (3GdJNWjW GdZPGFjs; (3GdJfejI GdRQGYjIs